Field Measurements of a Hybrid DVB-SH Single Frequency Network With an Inclined Satellite Orbit - Wilkus, S A; Bailey, J D; Brown, D G; Dave, R; Dorn, R L; Hanriot, J; Hoffman, M; Kulkarni, A; Lee, C S; Meader, L R; Polakovic, J M; Sullivan, J (IEEE transactions on broadcasting, 2010)
Field measurements of a DVB-SH network with both satellite and terrestrial transmitters are presented. The system is a Single Frequency Network transmitting video streams to vehicular terminals with up to 4 branches of receiver antenna diversity. The signal is transmitted in the S-band at 2.1859 GHz with both time and frequency synchronization of the terrestrial repeaters with the satellite's signal. The time and frequency variations are cancelled out at the satellite gateway, but because these can not be canceled at all locations, and because the satellite's position in space is variable (in an inclined orbit) the terrestrial repeaters are made to cancel the residual time and frequency variation. The field measurements include data taken in late 2008 through 2009 with multiple repeaters located in several cities including Las Vegas, NV, Raleigh and Durham, NC, as well as various morphologies, and with elevation angles to the satellite ranging from 25 ° to 52 ° . This paper presents coverage data for these various morphologies, modulation and code rates, as well as various MPE-iFEC interleaver settings used to ameliorate the effects of long shadowed intervals such as when the vehicle goes under highways or bridges where there signal is obscured for several seconds. We observed excellent performance in hybrid mode with better than 99% of the measured seconds error free. In satellite-only mode, the MPE-iFEC interleaver raised the performance from 81% to 91% averaged over all environments, including dense urban.